2008
DOI: 10.1007/s11858-008-0138-4
|View full text |Cite
|
Sign up to set email alerts
|

Lesson study in Asia Pacific classrooms: local responses to a global movement

Abstract: Japanese Lesson Study is a model for teacher professional learning that has recently attracted world attention particularly within the mathematics education community. It is a highly structured process of teacher collaboration, observation, reflection and practice. The world focus has been mainly due to the work of American researchers such as Stigler and Hiebert (Am Educ Winter:1-10, 1998; The teaching gap: Best ideas from the world's teachers for improving education in the classroom. Free Press, New York 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 10 publications
1
26
0
Order By: Relevance
“…Some of the research results that support this study include White & Lim (2008) which shows that lesson study is an activity in which educators can develop learning development processes and professional skills in improving student learning outcomes. Haratua et al (2011: 49) concluded that the implementation of lesson study can improve the quality of lecture results.…”
Section: Introductionsupporting
confidence: 55%
“…Some of the research results that support this study include White & Lim (2008) which shows that lesson study is an activity in which educators can develop learning development processes and professional skills in improving student learning outcomes. Haratua et al (2011: 49) concluded that the implementation of lesson study can improve the quality of lecture results.…”
Section: Introductionsupporting
confidence: 55%
“…Ebaeguin (2015) then used this analysis to develop a culturally embedded approach to promoting teacher growth through Lesson Study in a Philippine public school. These studies suggest that research could usefully focus on understanding better how Lesson Study can be recontextualised in different cultural contexts (see White and Lim 2008).…”
Section: Lesson Studymentioning
confidence: 99%
“…These include: appropriate content and pedagogical knowledge of teachers (Chokshi and Fernandez 2004;Yoshida, 2012); developing inquiry stances such as critical lens as researcher, critical lens as curriculum developer, and critical lens as student (Fernandez et al 2003); mindset of developing lesson plans with a holistic perspective; classroom observation with a focus on student learning (Watanabe 2002); teachers' commitment (White and Lim 2008;Verhoef et al 2014); having knowledgeable others' input (Chokshi and Fernandez 2004;Takahashi 2014), availability of high quality resources (White and Lim 2008;Yoshida 2012); and an authentic, inquiry-based professional learning community with a focus on teacher and student learning (Doig and Groves 2011;Perry and Lewis 2009). For example, Fernandez et al (2003) described three critical lenses for effectively conducting LS.…”
Section: Micro Level Conditionsmentioning
confidence: 99%